Prevalence of fungal colonization among patients with psoriasis in difficult-to-treat areas: impact of apremilast on mycotic burden and clinical outcomes - Campione, Elena; Cosio, Terenzio; Pistoia, Enrico Salvatore; Artosi, Fabio; Shumack, Ruslana Gaeta; Borselli, Cristiana; Rivieccio, Antonia; Caputo, Valerio; Favaro, Marco; Sorge, Roberto; Pica, Francesca; Bianchi, Luca; et al. (Frontiers in Immunology, 2024)
IntroductionFungi, including Candida, may be a trigger or exacerbate psoriasis, especially in difficult to treat (DTT) areas, through the activation of IL-17/23 axis.MethodsIn this study, seventy patients with DDT psoriasis were enrolled to evaluate Candida species and/or other opportunistic fungi colonization rate at baseline (T0) and the impact of apremilast on fungal load, clinical outcome, serum cytokine levels and biochemical serum profile of patients after 16, 24 and 52 weeks of treatment.ResultsIn our population, 33 (47%) patients were colonized by Candida spp. at baseline. In 24 (34%) individuals Candida was detected in the oral cavity while in the remaining 9 (13%) individuals the fungus was isolated from stool samples. Twenty subjects were colonized by only the species C. albicans, whereas in the remaining 13 a combination of two or more species (C. albicans plus non-albicans strains) was found in the oral cavity. Moreover, 27 (39%) patients were affected by onychomycosis. At 52 weeks, apremilast treatment induced a full recovery from Candida colonization in 83% of patients colonized with a single species of Candida (C. albicans); while in those co-infected by two or more Candida spp. induced a significant reduction (colony counts >10 CFU/mL) in fungal load was observed in comparison to baseline. Among patients with onychomycosis, 78% (21/27) of them presented a complete clinical resolution of nail psoriasis and concomitant nail infections. Finally, improvements in clinical scores i.e., PASI, NAPSI, DLQI, itch VAS, PAIN VAS, scPGA and sPGA-G and biochemical serum profile, as well as a significant decrease in serum IL-17A, TGF-β 1 and IL-10 levels (from 8.51 to 4.16 pg/mL; from 66.10 to 48.70 ng/mL and from 20.05 to 14 pg/mL, respectively) were observed in all patients.ConclusionsFungi may play a role in the psoriasis pathogenesis. Apremilast has been shown to ameliorate psoriasis signs and symptoms and counteract fungal overgrowth, probably by dampening inflammation, triggered by the fungal infections themselves. Thus, apremilast may represent an effective therapeutic approach in the treatment of DTT psoriasis and modulate the fungal colonization.